2018
DOI: 10.3928/23258160-20180831-08
|View full text |Cite
|
Sign up to set email alerts
|

Visual Acuity Outcomes in Diabetic Macular Edema With Fluocinolone Acetonide 0.2 μg/Day Versus Ranibizumab Plus Deferred Laser (DRCR Protocol I)

Abstract: In pseudophakic and chronic DME subgroups, FAc was comparable to ranibizumab plus deferred laser with fewer injections. [Ophthalmic Surg Lasers Imaging Retina. 2018;49:698-706.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Several clinical trials demonstrated high safety and efficacy of ranibizumab in the management of DME, exploring the usage of ranibizumab in different modalities and concentrations, as well as alone or in combination with laser, including READ-2 [ 77 ], RESOLVE [ 78 ], RESTORE [ 79 ], RISE and RIDE [ 80 ], LUCIDATE [ 81 ], REVEAL [ 82 ], RELIGHT [ 83 ], RETAIN [ 84 ] and READ-3 [ 85 ]. DRCR network conducted several multicenter clinical trials analyse similarities and differences of ranibizumab, with respect to other approaches, including other anti-VEGF molecules, corticosteroids, or laser, in the management of DR: Protocol S (ranibizumab vs. laser in PDR) [ 86 , 87 ], Protocol T (ranibizumab vs. aflibercept vs. bevacizumab in DME) [ 88 ] and Protocol I (fluocinolone acetonide vs. ranibizumab plus deferred laser in DME) [ 89 ] studies. Other meaningful clinical trials involving ranibizumab were: TREX-DME (ranibizumab “treat and extend” regimen with or without laser in DME) [ 90–92 ], ROTATE (ranibizumab in persistent DME after bevacizumab treatment) [ 93 ], RELATION (ranibizumab plus laser vs. laser alone in DR) [ 94 ] and REFINE (ranibizumab vs. laser in DME) [ 95 ] studies.…”
Section: Anti-vascular Endothelial Growth Factor Moleculesmentioning
confidence: 99%
“…Several clinical trials demonstrated high safety and efficacy of ranibizumab in the management of DME, exploring the usage of ranibizumab in different modalities and concentrations, as well as alone or in combination with laser, including READ-2 [ 77 ], RESOLVE [ 78 ], RESTORE [ 79 ], RISE and RIDE [ 80 ], LUCIDATE [ 81 ], REVEAL [ 82 ], RELIGHT [ 83 ], RETAIN [ 84 ] and READ-3 [ 85 ]. DRCR network conducted several multicenter clinical trials analyse similarities and differences of ranibizumab, with respect to other approaches, including other anti-VEGF molecules, corticosteroids, or laser, in the management of DR: Protocol S (ranibizumab vs. laser in PDR) [ 86 , 87 ], Protocol T (ranibizumab vs. aflibercept vs. bevacizumab in DME) [ 88 ] and Protocol I (fluocinolone acetonide vs. ranibizumab plus deferred laser in DME) [ 89 ] studies. Other meaningful clinical trials involving ranibizumab were: TREX-DME (ranibizumab “treat and extend” regimen with or without laser in DME) [ 90–92 ], ROTATE (ranibizumab in persistent DME after bevacizumab treatment) [ 93 ], RELATION (ranibizumab plus laser vs. laser alone in DR) [ 94 ] and REFINE (ranibizumab vs. laser in DME) [ 95 ] studies.…”
Section: Anti-vascular Endothelial Growth Factor Moleculesmentioning
confidence: 99%
“…The calculation of AUC has been described previously. 17,18 AUC was based on BCVA as this was the primary outcome in both FAME 16 and MEAD trials. 3 AUC for MEAD and FAME trials were based on BCVA letter score from baseline through to final visit (36 months in the FAME trial and 39 months in the MEAD trial).…”
Section: Auc Calculationmentioning
confidence: 99%
“…Mean AUC was then calculated using individual patient AUC values. 18 AUC for DEX was obtained from published data. [12][13][14] In the FAME trial, the observed change in BCVA letter score from baseline through to Month 36 was used to calculate AUC using the trapezoidal rule.…”
Section: Auc Calculationmentioning
confidence: 99%
See 2 more Smart Citations